The Historical Jesus and the Law The Form of His Activity and the Impact of Social Reputation - Ferda, Tucker S. (2018)
Historical Jesus research has traditionally concentrated on reconstructing Jesus' intentions and discerning his views on particular topics. That is especially true when it comes to the question of Jesus' relationship to the law of Moses. The dominant question driving scholarly discussion is this: What did Jesus think and teach in respect to the law? While the attempt to answer that question is important and should continue, I contend that a narrow focus on Jesus' thoughts and intentions struggles to account for the extent of controversy surrounding Jesus in his ministry. That controversy is better explained on the grounds that Jesus had developed the perception in some quarters of being a radical and a lawbreaker, even though we can be confident, as much of modern scholarship has shown us, that he aimed to uphold the law.
Keywords: aims of Jesus; Bible. Gospels; Church History; controversy narratives; Historical Jesus; Itinerancy; ITINERANCY (Church polity); Jesus Christ; Jewish Law; law of Moses